The Extent of the Independence of the International Criminal Court before the Authorities of the Security Council - An Analytical Study - Aziz, Peshraw Hamajan; Hassan, Karzan Ezzat (Journal of Legal and Political Studies, 2014)
International Criminal Court Appeared as a body responsible for criminal justice , as a result of the development of location of the individual in international law on the one hand and blatant violations of international humanitarian law on the other hand ,it is the first international organ works permanently for accountability and prosecution of persons responsible for international crimes , therefore, crimes that fall within the jurisdiction of this Court which in turn form a threat to international peace and security serves as a connect tool with the Security Council and ICC, and are entitled to the Security Council in accordance with Article (16 ) of the Statute to stop the investigation and trial for a period of 12 months , subject to renewal , and this lead to the emergence of negative effect to the Security Council on ICC, which is a negative impact on the functions and activity where the political interests of the Member States of the Security Council , especially the interests of the permanent members of the control and dominate the independence of goals and tasks of this Court and this leads to the demise and the loss of the court international Criminal Tribunal.
Keywords: International Criminal Court; responsibility; peace and security; Crime